Fermentation Driven Enhancement of Flavonoid, Phenolic, and Antioxidant Activity in Melastoma malabathricum Fruit - Maharani Maharani; Arif Setiawansyah; Mauritz Pandapotan Marpaung; Meliasi Nora Pratamarta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Senggani (Melastoma malabathricum L.) is a fruit known for its high content of phenolic and flavonoid compounds, which contribute to its antioxidant properties and are highly affected by fermentation processes. This study investigated how aerobic and anaerobic fermentation influence the total phenolic content, total flavonoid content, and antioxidant activity of senggani fruit extracts. The experiment involved aerobic fermentation without yeast and anaerobic fermentation with yeast, both conducted for three days. Total phenolics were quantified using the Folin–Ciocalteu assay, total flavonoids were measured via the aluminum chloride colorimetric method, and antioxidant activity was evaluated through the DPPH radical scavenging assay using UV–Vis spectrophotometry. The findings indicated that aerobic fermentation resulted in greater total phenolic (16.45 mg GAE/g) and flavonoid levels (16.95 mg QE/g), along with stronger antioxidant activity (IC50 55.37 ppm), compared to anaerobic fermentation. In contrast, anaerobic treatment yielded lower phenolic (11.77 mg GAE/g) and flavonoid contents (11.53 mg QE/g) and reduced antioxidant capacity (IC₅₀ 59.86 ppm). Overall, the results suggest that fermentation conditions play a crucial role in shaping the bioactive composition and antioxidant performance of senggani extracts, with aerobic fermentation showing better potential for developing functional and nutraceutical products.